Fenomena Film Dalam Keberagaman Seni Peran dan Budaya - Syarief, Fauzi; Susana, Susana; Pramanta Putra, Jaqualine (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
This research suggests an actor or actress, i.e. how an actor or actress in the role of a local character in a movie that was themed cultural diversity. The researchers used a qualitative research method with the approach of the study of Phenomenology that became a phenomenon and how the experience of an actor or actress in the role of animates to look realistic se maybe. Social construction theory researchers wear property of Peter l. Berger. These studies resulted that in any one actor or role animates actresses observational or should do the work directly into the field in order to adapt to the environment that will be lakoninya later especially in a movie that was themed cultural diversity, with different cultural dipeankan it be a challenge or a valuable experience of an actor or actress himself because it can know how the sense of difference from a variety of cultures